(untitled) (Sport and Exercise Psychology, 2025)
Alpine and freestyle skiing are sports disciplines that combine technical skill, physical strength, and mental endurance, representing one of the most fascinating and complex challenges in the world of winter sports. Adapting to environmental variables, such as snow and weather conditions, along with the need to make quick and precise decisions, requires athletes to have not only meticulous physical preparation but also robust psychological support. In recent years, mental preparation has emerged as a crucial element for success in skiing competitions, becoming equal in importance to physical training. This work also explores effective psychological strategies for optimizing skier performance, focusing on mental training techniques that can enhance concentration, stress management, and resilience during competitions. A further aspect examined by this work concerns the contribution that appropriate psychological methodologies can make to injury prevention and recovery. Finally, a key objective has been to provide an overview of recent scientific literature and to contribute to the understanding of the importance of mental preparation and its practical applications in training and competition, highlighting how an integrated approach can lead to improved results and a more fulfilling athletic experience for athletes.